CXCR4 signaling at the ovine fetal–maternal interface regulates vascularization, CD34+ cell presence, and autophagy in the endometrium†. Issue 1 (20th April 2019) - Runyan, Cheyenne L; McIntosh, Stacia Z; Maestas, Marlie M; Quinn, Kelsey E; Boren, Ben P; Ashley, Ryan L
Abstract: Placenta development is characterized by extensive angiogenesis and vascularization but if these processes are compromised placental dysfunction occurs, which is the underlying cause of pregnancy complications such as preeclampsia and intrauterine growth restriction. Dysregulation of placental angiogenesis has emerged as one of the main pathophysiological features in the development of placental insufficiency and its clinical consequences. The signaling axis initiated by chemokine ligand 12 (CXCL12) and its receptor CXCR4 stimulates angiogenesis in other tissues, and may be central to placental vascularization. We hypothesized that CXCL12-CXCR4 signaling governs the pro-angiogenic placental microenvironment by coordinating production of central angiogenic factors and receptors and regulates endometrial cell survival essential for placental function and subsequent fetal longevity. The CXCR4 antagonist, AMD3100, was used to elucidate the role of CXCL12-CXCR4 signaling regarding uteroplacental vascular remodeling at the fetal–maternal interface. On day 12 postbreeding, osmotic pumps were surgically installed and delivered either AMD3100 or PBS into the uterine lumen ipsilateral to the corpus luteum. On day 20, endometrial tissues were collected, snap-frozen in liquid nitrogen, and uterine horn cross sections preserved for immunofluorescent analysis. In endometrium from ewes receiving AMD3100 infusion, the abundance of select angiogenic factors was diminished, while presence of CD34+ cells increased compared to control ewes. Ewes receiving AMD3100 infusion also exhibited less activation of Akt/mTOR signaling, and elevated LC3B-II, a marker of cellular autophagy in endometrium. This study suggests that CXCL12-CXCR4 signaling governs placental homeostasis by serving as a critical upstream mediator of vascularization and cell viability, thereby ensuring appropriate placental development. Abstract : Inhibiting CXCR4 signaling at the fetal–maternal interface during initial placentation results in locally diminished vascularization, suppressed Akt/mTOR signaling, and increased autophagy.